THE IMPACT OF MOTIVATION IN USING ONLINE SHOPPING CART ON THE FREQUENCY OF USING ONLINE SHOPPING CART WITH THE ONLINE SHOPPING FREQUENCT - Gina Muliana Citra; Dudi Anandya (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
The number of e-commerce in Indonesia allows consumers to make purchases, simply by selecting and putting the desired item in the online shopping cart and proceed with the payment process then the consumer just waiting for the item he wants to arrive at home. This study aims to determine the influence of online shopping cart use motivation to the frequency of online shopping cart use with the frequency of online buying. This research was conducted by distributing the questionnaire online to 120 respondents. From the results of this study conducted data processing with AMOS 23.0 to prove the influence of each research variable. The result of research shows that current purchase intent, taking advantage of price promotion has positive and significant effect of frequency of online shopping cart use and current purchase intent have a positive and significant effect of frequency of online buying. While entertainment purpose, organizational intent, and research and information search have no significant effect on the frequency of online shopping cart use.